Gata4 and Gata5 Cooperatively Regulate Cardiac Myocyte Proliferation in Mice - Singh, Manvendra K. (American Society for Biochemistry and Molecular Biology, 2010)
GATA5 is a member of the zinc finger transcription factor GATA family (GATA1–6) that plays a wide variety of roles in embryonic and adult development. Experiments in multiple model systems have emphasized the importance of the GATA family members 4–6 in the development of the endoderm and mesoderm. Yet despite overlapping expression patterns, there is little evidence of an important role for GATA5 in mammalian cardiac development. We have generated a new Gata5 mutant allele lacking exons 2 and 3 that encodes both zinc finger domains (Gata5(tm)(2)(Eem)), and we show that although Gata5(−/−) mice are viable, Gata4(+/−)5(−/−) mutants die at mid-gestation and exhibit profound cardiovascular defects, including abnormalities of cardiomyocyte proliferation and cardiac chamber maturation. These results demonstrate functional redundancy between Gata4 and Gata5 during cardiac development and implicate Gata5 as a candidate modifier gene for congenital heart disease.